E-ASSESSING LEARNING OUTCOMES: PROPOSAL FOR A PRACTICAL TOOL - TALOE - Alfredo Soeiro (2014)
The world has been experiencing rapid transformation in Education area and on the actual scenario mobility, cooperation and development of quality relating to methods of assessment are crucial subjects that raise many questions. Effective assessment drives learning efficiency as the growth of e-learning technologies drives e-assessment. This growth of using e-learning reinforces the need to improve learning and support the idea that is important to define a strategy to ensure that the selection of assessment methods responds positively to the objectives and outcomes of the course programme. This will facilitate a clear evaluation of competencies, skills and knowledge acquired during the learning or training. Facing this scenario a project, Time to Assess Learning Outcomes in E-learning - TALOE, intends to promote the internal consistency of online courses. It was financed by the European Commission for the years of 2014-15. It uses an existing tool called the ALOA model (Aligning Learning Outcomes and Assessment). This tool highlights the connection between the intended learning outcomes and the assessment strategy used during a course. It is a fact that not all assessment methods are valid for each type of the learning outcomes. The ALOA model provides tools for linking learning outcomes and assessment tasks. The TALOE project intends to materialize the application of the ALOA tools to the specific context of e-learning. The main goal of TALOE is to develop a web-based platform to help teachers and trainers decide on the e-assessment strategies to use in their online courses. The rationale of TALOE is that a teacher/trainer will describe the learning outcomes of the course or module and the TALOE platform will analyse them and provide an e-assessment strategy that is consistent with the set of intended learning outcomes. To be able to develop the practical tool the TALOE consortium will develop and achieve the following specific goals: a) Research and select innovative e-assessment practices that take advantage of the use of technology; b) Develop a web-based tool that is easy to use by the stakeholders; c) To test the implementation of the tool with real case studies; d) To distribute and disseminate the TALOE tool among the communities of stakeholders.